Antibacterial Activity of 2′-Esters of Erythromycin - Tardrew, P. L. (1969)
The effect of esterification at the 2′-position of desosamine on the antibacterial activity of erythromycin was investigated by determining the bacteriostatic and bactericidal activities of erythromycin and a number of its 2′-esters on S. aureus and relating these activities to the hydrolysis rates of the esters. These studies, together with comparison of the inhibition of protein synthesis in a cell-free system isolated from S. aureus, lead to the conclusion that 2′-esters of erythromycin are inactive until hydrolyzed. Loss of activity appears to result from inability of erythromycin esters to bind to bacterial ribosomes and thus inhibit synthesis of protein.